1995
DOI: 10.1007/bf02401854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in mitochondrial DNA of the screwworm,Cochliomyia hominivorax (Diptera: Calliphoridae), from Brazil

Abstract: Restriction fragment length polymorphism (RFLP) analysis of mitochondrial DNA (mtDNA) was used to examine genetic variation and population structure of screwworm flies in four populations from São Paulo State, Brazil. The total DNA of 405 individuals was digested with 15 restriction endonucleases and probed with five cloned HindIII fragments representing the entire mitochondrial genome of Cochliomyia hominivorax. The survey revealed that four enzymes (HaeIII, HindIII, MspI, and PvuII) were suitable to detect m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 31 publications
0
3
1
2
Order By: Relevance
“…Sequence divergences between H. irritans and H. exigua (1.8ῌ1.9ῌ) in the present study are larger than the range of the estimated values for intraspecies di#eren-tiation based on mtDNA in various insect species which have been reported by DeSalle et al (1986), Martin and Simon (1990), and Vargas and Espin (1995). mtDNA analysis of haplotypes of the calliphorid flies Chrysomya albiceps and C. rufifacies (which are closely related to each other) showed 0.04ῌ0.8ῌ intraspecies di#erences and 2.9ῌ3.1ῌ interspecies di#erences (Wells and Sperling, 1999).…”
Section: D>h8jhh>dccontrasting
confidence: 79%
“…Sequence divergences between H. irritans and H. exigua (1.8ῌ1.9ῌ) in the present study are larger than the range of the estimated values for intraspecies di#eren-tiation based on mtDNA in various insect species which have been reported by DeSalle et al (1986), Martin and Simon (1990), and Vargas and Espin (1995). mtDNA analysis of haplotypes of the calliphorid flies Chrysomya albiceps and C. rufifacies (which are closely related to each other) showed 0.04ῌ0.8ῌ intraspecies di#erences and 2.9ῌ3.1ῌ interspecies di#erences (Wells and Sperling, 1999).…”
Section: D>h8jhh>dccontrasting
confidence: 79%
“…Hasegawa (1995) [11] observed 44.7% average polymorphism in workers and queen's sperm and concluded the father's information is important to identify the true parents-offspring relationship by RAPD. To study relatedness among and within the honey bee colony mitochondrial DNA diversity was studied in Apis species (Cornuet and Garney, 1991; Magnus et al, 2014) [4,19] and in Screwworm by Infante and Espin 1995 [14] . Black et al, (1992) [3] found lesser and greater genetic variation among Aphid pisum individuals of different colour by using different primers in RAPD.…”
Section: Discussionmentioning
confidence: 99%
“…Kin selection hypothesis of Hamilton (1964) [10] regarding evolution of Eusociality in hymenopteran insects gives importance to male haploidy and observed high genetic relatedness among sibling. To detect genetic relationship between individual populations several molecular methods like allozyme marker detection, DNA fingerprinting, RFLP, RAPD, Hormones are in use (Woyke, 1975;Pamilo et al, 1978b;Welsh and Mccleland, 1990;Mortiz et al 1991; Infante and Espin 1995; Barsagade and Jiwatode, 2021) [42,26,40,25,14,2] . To study genetic variation in insects, RAPD is suitable technique as compared to other molecular marker technique due to low requirement of DNA sample, no previous knowledge of primer sequence and no hazards of radioactivity (Williams et al, 1990) [41] .Various researchers found that RAPD markers are convenient tools to study genetic variation in Hymenopteran insects (Hasegawa 1995; Lu and Rank 1996) [11,17] and in other organisms (Welsh and Mccleland, 1990;Williams et al, 1990) [40,41] .…”
Section: Introductionmentioning
confidence: 99%
“…For each population, 15-17 individuals, from at least 10 wounds, were analyzed to determine the presence of mutations. DNA from larvae was extracted using the phenol-chloroform method, according to Vargas and Espin (1995).…”
Section: Populations Sampled and Dna Extractionmentioning
confidence: 99%